A New Method for Controlling Rockbursts in the Mining Roadway of Ultrathick Coal Seams Based on the Dual Pressure Relief Method. (29th August 2021) - Yu, Guangyuan; Wang, Jiong; Ma, Zimin; Ming, Wei; Ma, Xingen
Abstract : To control rockbursts in mining roadways in ultrathick coal seams, a new method for preventing rockbursts through dual pressure relief by roof cutting through cumulative blasting in medium-deep boreholes from the conveyor gateway and return airway was proposed. The mechanical characteristics of key overlying strata of the working face under the effect of dual pressure relief were theoretically investigated. Furthermore, a mathematical relationship between the roof-cutting depth and the advanced abutment pressure on the working face was established to reveal the mechanism of dual pressure relief in controlling rockbursts. Moreover, the effect of the dual pressure relief method on controlling rockbursts was validated through numerical simulation and field testing. Results showed that artificially increasing the caving height of gangues in goaf based on the dual pressure relief method can restrict the subsidence of key strata, thus reducing the advanced abutment pressure of the working face; the method influences a range of 20 m in front of the working face along the strike and areas 30 m away from the two roadways along the dip. The average energy density of coal in the side of the conveyor gateway is decreased by 15.4%, while that in the side of return airway is reduced by 13.8% within the range of influence. The field test results indicated that the average pressure on support declines by 21.4% within 30 m from the working face to the conveyor gateway, while it decreases by 20.5% within that region 25 m from the return airway by using the dual pressure relief method. After conducting dual pressure relief, the total number of microseismic (MS) events during mining of the working face is decreased by 25.4%. The number of MS events with energy release exceeding 10 3 J falls by 36.6%, while the number of events releasing less than 10 3 J is increased by 28.6%. The characteristics of MS energy release change from coexistence of low-energy events and a small number of high-energy events to the occurrence of numerous low-energy events. Results can verify the effectiveness of the dual pressure relief method in controlling rockbursts in the mining roadway of ultrathick coal seams.